Association Between a Low Ankle–Brachial Index and Dementia in a General Elderly Population in Central Africa (Epidemiology of Dementia in Central Africa Study). Issue 7 (3rd June 2013) - Guerchet, Maëlenn; Mbelesso, Pascal; Mouanga, Alain M.; Tabo, André; Bandzouzi, Bébène; Clément, Jean‐Pierre; Lacroix, Philippe; Preux, Pierre‐Marie; Aboyans, Victor
<x xml:space="preserve">Abstract</x> Objectives To investigate the association between peripheral arterial disease (PAD) and dementia in native elderly African populations. Design Two successive door‐to‐door cross‐sectional surveys in the general population. Settings Representative districts of Bangui (Central African Republic) and Brazzaville (Republic of Congo). Participants Population aged 65 and older. Measurements Peripheral arterial disease was defined as an ankle–brachial index (ABI) of 0.90 or less. Cognitive screening was performed using the Community Screening Interview for Dementia and the Five‐Word Test. Diagnosis of dementia was confirmed after further neuropsychological tests and neurological examination according to the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition, criteria. Multivariate logistic regression models were used to quantify the association between PAD and dementia in those populations, with adjustments for cardiovascular disease (CVD) and other variables. Results A significant association was observed between PAD and prevalent dementia (odds ratio (OR) = 2.43, 95% confidence interval (CI) = 1.44–4.13, P = .001), even after adjustment for age, city, sex, CVD risk factors, education, and depressive disorders (OR = 2.37, 95% CI = 1.31–4.26, P = .004). This association was stronger with lower ABI. Conclusion These findings support the hypothesis of a link between atherosclerosis (represented by a low ABI) and cognitive disorders in native Africans and are similar to previous reports in African Americans and other ethnic groups.